Flint Hills' Night Sky - Dave Clark (Symphony in the Flint Hills, 2009)
We can still see the sky the way our ancestors and Native Americans did. It is still there, unchanged. Because of light pollution, for many people it is a whole new realm to be discovered. It is as much a part of the prairie as the land and animals and deserves just as much to be experienced. It's important to hold on to all of our heritages and the awe, serenity, soul, and profundity of the heavens are among those heritages.
Keywords: sky; stars; night; Big Stretcher; Kansas; native; tradition; historic; rituals; Polaris; Native Americans; Indian; people; tribes; cardinal; Flint Hills; heavens; earth